The lost sun - Gratton, Tessa. (The United States of Asgard ;, 2013)
"In an alternate U.S.A. (the United States of Asgard), Soren Bearskin, the son of an infamous beserker, and Astrid Glyn, daughter of a renowned seer, embark on a road trip to find Baldur, the missing god whose absence has caused panic throughout the country."--